To rearrange the slope formula \( y = mx + b \) for the quantity of interest \( m \), we will isolate \( m \) on one side of the equation. Here are the steps:
-
Start with the original equation: \[ y = mx + b \]
-
Subtract \( b \) from both sides to isolate the term involving \( m \): \[ y - b = mx \]
-
Divide both sides by \( x \) to solve for \( m \): \[ m = \frac{y - b}{x} \]
Now, the slope \( m \) is isolated: \[ m = \frac{y - b}{x} \]
This is the rearranged formula for \( m \) in terms of \( y \), \( b \), and \( x \).